Pregravid training in patients with the operated ovaries in assisted reproductive technologies program - K G Serebrennikova; E S Vanke; E P Kuznetcova; T V Ivanova; Yu V Miloslavskiy (IP Berlin A.V., 2015)
Pregravid training (PT) is an urgent problem in reproductology and is a complex of measures aimed at the favorable outcome of pregnancy and childbirth. Carrying out the PT allows to increase the percentage of pregnancy and reduce the risk of complications. PT is of great importance in patients who underwent surgery on the ovaries, because it is the primary mechanism that can improve the performance of pregnancy and childbirth in ART programs.